Assessment of plasma B-type natriuretic peptide and highly sensitive C- reactive protein among diagnosed patients of diabetes mellitus with and without cardiovascular disease - Smriti Rai,; Mingma Lhamu Sherpa,; Bidita Khandelwal,; Sameer Bhandari,; Richen Doma Bhutia, (Asian Journal of Medical Sciences, 2024)
Background: Considering the burden of cardiovascular disease (CVD) complications in patients with diabetes and the production of BNP on the incidence of CVD. Aims and Objectives: We investigated the role of BNP and high sensitive C-reactive protein (hs-CRP) in predicting the presence of CVD in diabetes and determined if the concentration load of BNP and hs-CRP differed in diabetics participants with CVD and without CVD. Materials and Methods: Diabetic consenting participants fitting the study inclusion criteria were enrolled. Based on medical records, participants were grouped into diabetes with CVD and diabetes without CVD and tested for blood BNP, hs-CRP, Lipid Profile, and hemoglobin A1C (HbA1C). Results: Diabetes mellitus (DM) was relatively higher in the age group of 51–60 years with female preponderance. Ethnic distribution demonstrated a high percentage of DM among the Sikkimese Nepalese, followed by Bhutias, and Lepchas. On ascertaining the effects of BNP and hs-CRP on the likelihood that the diabetic participants have CVD, only BNP demonstrated statistical significance. However, unlike hs-CRP, BNP exhibited no association with HbA1C and lipid parameters. BNP and hs-CRP levels were higher among diabetics with CVD when compared to diabetics without CVD. Conclusion: Increasing BNP levels in diabetes is associated with an increased likelihood of exhibiting CVD but increasing hs-CRP level may not be associated with an increased likelihood of exhibiting CVD. Increase in BNP levels independent of influence by HbA1C and lipid profile should be investigated further and yet importantly diabetes with CVD exhibits extra inflammatory load (hs-CRP) compared to diabetes without CVDs.